Prevalence Of Obesity and Its Associated Co Morbidities Amongst Adults - Jayashree Sachin Gothankar (Medsci Publications, 2011)
Objective: To evaluate association of obesity with common co morbidities like hypertension and type 2 diabetes mellitus. Background: Obesity has reached epidemic proportions in India. The health consequences of obesity range from increased risk of premature death to serious chronic conditions like hypertension and type 2 diabetes which reduces overall quality of life. BMI and waist circumference are useful guide to assess obesity related health risks. Material and methods: A cross sectional study done on 53 adult subjects attending diabetes and hypertension detection camp organized at an urban health training center of a private Medical College , Pune. Results: Prevalence of obesity was 43 % among adults. There was statistically significant association between BMI (>=25) and diabetes (p<0.05) and BMI and hypertension (p<0.05).In females central obesity (waist circumference >=80) was statistically associated with diabetes and hypertension. Diabetes and hypertension did not found to be associated with central obesity in male (p>0.05). Conclusion: Obesity as assessed by BMI and waist circumference is associated with hypertension and diabetes. Thus approaches to reduce the risk of developing hypertension and diabetes may include prevention of overweight and obesity.